Survival and Associated Risk Factors for Mortality Among Infants with Critical Congenital Heart Disease in a Developing Country - Mat Bah, Mohd Nizam; Sapian, Mohd Hanafi; Jamil, Mohammad Tamim; Alias, Amelia; Zahari, Norazah (Springer Verlag, 2018)
Critical congenital heart disease (CCHD) is associated with significant morbidity and mortality. However, data on survival of CCHD and the risk factors associated with its mortality are limited. This study examined CCHD survival and the risk factors for CCHD mortality. Using a retrospective cohort study of infants born with CCHD from 2006 to 2015, survival over 10 years was estimated using Kaplan–Meier analysis, and the risk factors for mortality were analyzed using multivariate Cox proportional hazards regression. A total of 491 CCHD cases were included in the study, with an overall mortality rate of 34.8% (95% confidence interval [CI] 30.6–39.2). The intervention/surgical mortality rate was 9.8% ≤ 30 days and 11.5% > 30 days after surgery, and 17% died before surgery or intervention. The median age at death was 2.7 months [first quartile: 1 month, third quartile: 7.3 months]. The CCHD survival rate was 90.4% (95% CI 89–91.8%) at 1 month, 69.3% (95% CI 67.2–71.4%) at 1 year, 63.4% (95% CI 61.1–65.7%) at 5 years, and 61.4% (95% CI 58.9–63.9%) at 10 years. Weight of < 2 kg at diagnosis, associated syndromes, poor pre-operative condition, and non-duct-dependent CCHD were independent risk factors for poor survival, with hazard ratios of 2.61, 2.10, 2.22, and 1.70, respectively. CCHD is associated with a high mortality rate. Low weight, poor pre-operative condition, associated syndromes, and non-duct-dependent CCHD are significant risk factors affecting the survival of infants with CCHD.